Interpretive Narrations in the Book of Al-Muntaqa by Ibn Al-Jaroud (307 AH) (A Jurisprudential Interpretive Study): Surah Al-Fatihah as an Example (Islamic Sciences Journal, 2024)
Praise be to Allah, the Lord of the Worlds, and the best blessings and peace be upon our master and beloved, the best of messengers, and upon his family and companions, peace and blessings be upon him.The subject of this thesis is entitled: (Interpretive Narrations in the Book of Al-Muntaqa by Ibn Al-Jaroud (307 AH), a Jurisprudential Interpretive Study), which I submitted to obtain a doctorate degree in the Department of Qur’anic Sciences and Islamic Education, College of Education for the Humanities, University of Anbar, where the number of exegetical narrations reached (305), (a narration, and each narration included an issue, or several issues, whether interpretive or jurisprudential, as my study  was to collect interpretive narrations and extract them from hadith books. Then, the interpretation of this narration is presented, and then the jurisprudential ruling that I dealt with was mentioned by presenting the sayings of the jurists, their evidence, and explaining the most correct opinion.In order for the reader to find it clear  what Allah the  Almighty means from the noble verses mentioned in the narration, and to reach an understanding of the meanings and legal rulings intended therein
Keywords: Narrations, interpretation, Al-Muntaqa, IbnJarud, jurisprudence, Surat Al-Fatiha.